Developing a Village Financial Governance Model: A Case Study of Maitara Tengah Village, Tidore Islands City, Indonesia - Ache, Samsul Bahri; Huseini, Martani (Borong Newinera Publisher, 2025)
This study explores the development of a village financial governance model in Indonesia, with a specific focus on Maitara Tengah Village, Tidore Islands City. It addresses four critical issues commonly encountered in village financial management: lack of transparency, weak accountability, limited community participation, and inadequate financial planning and reporting capacity. Employing a qualitative methodology, data were collected through interviews, field observations, and document analysis conducted between 2022 and 2024. The findings reveal that the effective use of village funds is constrained by limited administrative capacity, poor regulatory enforcement, and largely symbolic participatory mechanisms. To address these challenges, the research proposes a context-sensitive governance model that integrates principles of good governance, collaborative planning, and adaptive institutional design. The model aims to enhance transparency, accountability, and participatory engagement while accommodating the unique socio-cultural and geographic characteristics of remote and island communities. This study contributes to the broader discourse on village autonomy and decentralized rural development by offering a scalable and inclusive governance framework suited to the Indonesian context.